Prognostic Value of Coronary Microvascular Function Measured Immediately After Percutaneous Coronary Intervention in Stable Coronary Artery Disease: An International Multicenter Study. (September 2019) - Nishi, Takeshi; Murai, Tadashi; Ciccarelli, Giovanni; Shah, Sonia V.; Kobayashi, Yuhei; Derimay, François; Waseda, Katsuhisa; Moonen, Avalon; Hoshino, Masahiro; Hirohata, Atsushi; Yong, Andy S.C.; Ng, Martin K.C.; et al.
Abstract : Background: The prognostic impact of coronary microvascular dysfunction after percutaneous coronary intervention (PCI) remains unclear in patients with stable coronary artery disease. This study sought to investigate the prognostic value of microvascular function measured immediately after PCI in patients with stable coronary artery disease. Methods: We enrolled 572 patients with stable coronary artery disease who underwent PCI and elective measurement of the index of microcirculatory resistance (IMR) immediately after PCI from 8 centers in 4 countries. Impaired microvascular function was defined as IMR≥25 (high IMR). Major adverse cardiac events, including death, myocardial infarction (MI) and target vessel revascularization, were evaluated. Results: During a median follow-up duration of 4.0 years, the cumulative major adverse cardiac events rate was significantly higher in the high IMR group (n=66/148) compared with the low IMR group (n=128/424; hazard ratio [HR], 1.56; 95% CI, 1.16−2.105; P =0.001), primarily due to a higher rate of periprocedural MI (HR, 1.59; 95% CI, 1.11−2.28; P =0.004) but also due to higher rates of mortality (HR, 1.59; 95% CI, 0.76−3.35; P =0.22), spontaneous MI (HR, 2.10; 95% CI, 0.67−6.63; P =0.20) and target vessel revascularization (HR, 1.40; 95% CI, 0.77−2.54; P =0.27). Cumulative risk for death, spontaneous MI, and target vessel revascularization was higher in the high IMR group (HR, 1.55; 95% CI, 0.99−2.43; P =0.056), as was death and spontaneous MI alone (HR, 1.79; 95% CI, 0.96−3.36; P =0.065). On multivariable analysis, high IMR post-PCI was an independent predictor of major adverse cardiac events. Conclusions: IMR measured immediately after PCI predicts adverse events in patients with stable coronary artery disease. Abstract : Supplemental Digital Content is available in the text.